Biotribological behavior of MXene-UHMWPE composites - Marian, Max; Feile, Klara; Rothammer, Benedict; Bartz, Marcel; Wartzack, Sandro; Rosenkranz, Andreas (77th STLE Annual Meeting & Exhibition, 2023)
MXenes are a relatively new class of 2D transition metal carbides, nitridesand carbonitrides receiving increasing attention in tribologicalapplications due to their self-lubricating character. A prospectiveapplication of MXenes is their addition to UHMWPE with the overallpurpose to improve the biotribological behavior of polymericcomponents of load-bearing implants. Within this study, Ti3C2Tx-UHMWPE composites with varying MXene content were biotribologicallyanalyzed using pin-on-disk tribometer tests. Thereby, a friction reductionby up to 22% compared to pure UHMWPE was demonstrated. Thedetermined wear rates of the disks considerably decreased by up to 43%due to the addition of MXenes. Furthermore, the composite-disksreduced the wear rates of the tested CoCr-pins by up to 19%. Both the reduction of friction and wear underline the great potential of MXenes asa reinforcement phase in UHMWPE to improve the biotribologicalbehavior and service life of biomedical applicatio

Biotribological behavior of MXene-UHMWPE-composites for total knee arthroplasty - Feile, Klara; Rothammer, Benedict; Bartz, Marcel; Wartzack, Sandro; Marian, Max (5th YOUNG TRIBOLOGICAL RESEARCHER SYMPOSIUM, 2022)
MXenes are a relatively new class of two-dimensional transition metal carbides, nitrides and carbonitrides experiencing increasing attention for tribological applications. Due to their multi-layer structure with relatively weak inter-layer bonding, a self-lubricating character is enabled. A possible, but not yet explored, application of MXenes is the addition to UHMWPE with the aim to improve the biotribological behavior of tibial inlays of total knee arthroplasties (TKA). Within this study, Ti3C2Tx-UHMWPE-composites with 0.5 wt.‑%, 1.0 wt.‑% and 2.0 wt.‑% MXenes were biotribologically tested using a pin-on-disk tribometer in oscillating sliding mode lubricated with diluted bovine calf serum at 37 °C. Thereby, a reduction of the coefficient of friction by up to 22 % compared to pure UHMWPE was demonstrated and the determined wear rates of the disks decreased considerably by 25 % (0.5 wt.‑% and 1.0 wt.‑%) and 43 % (2.0 wt.‑%). Furthermore, the composite-disks reduced the wear rates of the tested Co28Cr6Mo-pins by up to 19 %. Both the reduction of friction and wear show the great potential of MXenes as a reinforcement phase to UHMWPE to improve the biotribological behavior of tibial inlays and thus, increase the service life of TKA in the long-ter

Einsatz von Maschinellem Lernen zur Vorhersage von Schmierfilmparametern in abweichungsbehafteten elastohydrodynamischen Linienkontakten - Feile, Klara; Bartz, Marcel; Wartzack, Sandro (65. Tribologie-Fachtagung 2024. Reibung, Schmierung und Verschleiß. Forschung und praktische Anwendungen., 2024)

Modeling of Shape Deviations for the Development of Predictive Models of TEHD Contacts - Feile, Klara; Bartz, Marcel; Wartzack, Sandro (24, 2024)

Prediction of Lubricant Film Parameters of Deviated EHL Line Contacts using Machine Learning Approaches - Feile, Klara; Bartz, Marcel; Wartzack, Sandro (7th YOUNG TRIBOLOGICAL RESEARCHER SYMPOSIUM, 2024)
Friction losses are, among other factors, significantly caused by manufacturing-related shape deviations of surface topographies, e.g. due to tool vibrations. Until now, the consideration of these shape deviations within the calculation of EHL contacts in the design process of low-friction machine elements with lubricated contacts has only been possible by means of complex and time-consuming numerical simulations. Consequently, the objective of this contribution is to utilize machine learning (ML) approaches in order to significantly accelerate the prediction of lubricant film parameters in 2D line contacts, while accounting for shape deviations in the form of waviness. The numerical simulations used to generate the training and test data sets are discussed first. Subsequently, Gaussian process regression and neural network models are compared, whereby the number of input parameters is reduced due to the use of dimensionless parameters. The results demonstrate the potential of ML models to predict lubricating film parameters quickly and precisely, even when taking shape deviations into accoun

Ti3C2Tx Solid Lubricant Coatings in Rolling Bearings with Remarkable Performance beyond State-of-the-Art Materials - Marian, Max; Feile, Klara; Rothammer, Benedict; Bartz, Marcel; Wartzack, Sandro; Seynstahl, Armin; Tremmel, Stephan; Krauß, Sebastian; Merle, Benoit; Boehm, Thomas; Wang, Bo; Wyatt, Brian C.; et al. (Applied Materials Today, 2021)
Two-dimensional (2D) transition metal carbides, nitrides, and carbonitrides, known as MXenes, are a growing class of 2D materials, which offer great solid lubrication ability for low friction applications due to their weakly bonded multi-layer structure and tribo-layer formation with self-lubricating characteristics. To date, most studies have assessed their tribological response in basic laboratory tests. However, these tests do not adequately reflect the complex geometries, kinematics, and stresses present in machine components. Here, we aim at bridging this gap through assessment of the friction and wear performance of multi-layer Ti3C2Tx MXene solid lubricant coatings used in rolling bearings. MXenes’ tribological response is compared with state-of-the art solid lubricant coatings, which include molybdenum disulfide (MoS2), tungsten-doped hydrogenated amorphous carbon (a‑C:H:W), and hydrogen-free, more graphite-like amorphous carbon (a‑C). Multi-layer Ti3C2Tx MXene coatings reduce wear on the bearing washers by up to 94 %, which can be attributed to the transfer of the lubricious MXene nano-sheets to secondary tribo-contacts of the bearing. While the frictional torque of all solid lubricant coatings is similar during steady-operation, the MXene-coated bearings extend the service life by 30 % and 55 % compared to MoS2 and DLC, respectively. This contribution demonstrates the ability of MXene solid lubricant coatings to outperform state-of-the-art solid lubricants in dry-running machine components such as rolling bearing
Keywords: 2D materials; MXenes; MoS2; DLC; solid lubrication; rolling bearings

Ti3C2Tx-UHMWPE nanocomposites—Towards an enhanced wear-resistance of biomedical implants - Rothammer, Benedict; Feile, Klara; Werner, Siegfried; Frank, Rainer; Bartz, Marcel; Wartzack, Sandro; Schubert, Dirk W.; Drummer, Dietmar; Detsch, Rainer; Wang, Bo; Rosenkranz, Andreas; Marian, Max (Journal of Biomedical Materials Research Part A, 2024)
There is an urgent need to enhance the mechanical and biotribological performance of polymeric materials utilized in biomedical devices such as load-bearing artificial joints, notably ultrahigh molecular weight polyethylene (UHMWPE). While two-dimensional (2D) materials like graphene, graphene oxide (GO), reduced GO, or hexagonal boron nitride (h-BN) have shown promise as reinforcement phases in polymer matrix composites (PMCs), the potential of MXenes, known for their chemical inertness, mechanical robustness, and wear-resistance, remains largely unexplored in biotribology. This study aims to address this gap by fabricating Ti3C2Tx-UHMWPE nanocomposites using compression molding. Primary objectives include enhancements in mechanical properties, biocompatibility, and biotribological performance, particularly in terms of friction and wear resistance in cobalt chromium alloy pin-on-UHMWPE disk experiments lubricated by artificial synovial fluid. Thereby, no substantial changes in the indentation hardness or the elastic modulus are observed, while the analysis of the resulting wettability and surface tension as well as indirect and direct in vitro evaluation do not point towards cytotoxicity. Most importantly, Ti3C2Tx-reinforced PMCs substantially reduce friction and wear by up to 19 and 44 %, respectively, which was attributed to the formation of an easy-to-shear transfer fil
Keywords: 2D materials; MXenes; UHMWPE; polymer matrix composites; biotribology